2018
DOI: 10.5194/bg-15-4367-2018
|View full text |Cite
|
Sign up to set email alerts
|

Improving the strength of sandy soils via ureolytic CaCO<sub>3</sub> solidification by <i>Sporosarcina ureae</i>

Abstract: Abstract. "Microbially induced carbonate precipitation" (MICP) is a biogeochemical process that can be applied to strengthen materials. The hydrolysis of urea by microbial catalysis to form carbonate is a commonly studied example of MICP. In this study, Sporosarcina ureae, a ureolytic organism, was compared to other ureolytic and non-ureolytic organisms of Bacillus and Sporosarcina genera in the assessment of its ability to produce carbonates by ureolytic MICP for ground reinforcement. It was found that S. ure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 55 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that the characteristic reflection patterns that arise from XRD analysis allow for reliable identification of calcite, as quartz grains display significantly different XRD patterns (Hupp & Donovan, 2018). It is a well‐known phenomenon that calcite plugs pores between sand particles and improves the mechanical properties of the resulting sand cubes (Huang et al, 2016; Wang & Liu, 2021; Whitaker et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the characteristic reflection patterns that arise from XRD analysis allow for reliable identification of calcite, as quartz grains display significantly different XRD patterns (Hupp & Donovan, 2018). It is a well‐known phenomenon that calcite plugs pores between sand particles and improves the mechanical properties of the resulting sand cubes (Huang et al, 2016; Wang & Liu, 2021; Whitaker et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This crystal type of CaCO 3 can not only significantly improve the strength and stiffness of soil, but also maintain the permeability of soil samples. Whitaker et al [132] found that S. ureae had a stronger curing capacity than S. pasteurii, which has been widely studied. When the researchers used S. ureae bacteria solution and added 0.5 M cementation solution, the direct shear strength of the solidified sandy soil increased from 15.77 kPa before solidification to 135.80 kPa.…”
Section: Concentration Of Cementation Solutionmentioning
confidence: 99%
“…Year % of 64 publications 2018; Li et al, 2018;van Paassen et al, 2010;Whiffin, 2004;Michael Whitaker et al, 2018;Wu et al, 2019) by enhancing the geomechanical properties. Furthermore, MICP has been applied to immobilization and bioremediation of contaminated sites, specifically by inorganic compounds (Jain and Arnepalli, 2019;Achal et al, 2012a;Mwandira et al, 2017;Achal et al, 2012b;Kasra and Erkurt, 2020).…”
Section: Anns Triaxial Approachmentioning
confidence: 99%